Use of a cobalt niobate-based material in blue pigments, blue glazes and method for their production
Patent Information
- Application Number
- CN202410338041.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-22
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-03-22
AI Technical Summary
但上述无机蓝色色料中,钒锆蓝V-ZrSiO4蓝色呈色较弱,不足以在正常掺量条件下(1~8wt%)显示出深色色调;钇铟锰蓝YIn1-xMnxO3、普鲁士蓝、群青蓝、磷酸盐Co3(PO4)2和天青石蓝存在不稳定、易分解的缺陷,无法应用于600~1200℃中高温环境;而尖晶石CoAl2O4和橄榄石Co2SiO4虽是业界广泛采用的高温蓝色色料,但其实际着色很大程度上来源于脱离于基质CoAl2O4或Co2SiO4并分散于釉中的Co2+离子,而非完全源于色料自身,这两种色料在单独纯相存在时,具有不错的稳定性,但应用于高温环境时,稳定性明显下降,致使色料本身变色,造成较大的色差,无法应用于600~1200℃中高温环境
[0025]本发明提供了一种铌酸钴基材料在蓝色色料中的应用,所述铌酸钴基材料的化学式为:Co1-xMxNb2O6,其中M为Mg、Ca、Zn、Sr和Ba中的一种;x为0~1。本发明所述铌酸钴基材料中,Co2+所在的晶体结构及其配位对色料的着色强度和色调有强烈的影响,其中Co2+处于扭曲的八面体位点,可见光区吸收谱带主要位于红、橙、黄三个光区,能反射大部分蓝色波段的可见光,因此显示出更纯正的蓝色;同时,Nb5+具备更高的价态,能够增强色料在釉中的呈色稳定性,可应用于600~1200℃的中高温环境,具有出色的耐高温性与鲜艳明丽的蓝色着色特性。
Smart Images

Figure CN118221346B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of inorganic pigment technology, specifically relating to the application of cobalt niobate-based materials in blue pigments, blue glazes and their preparation methods. Background Technology
[0002] Inorganic pigments possess a range of excellent physicochemical properties, including good weather resistance, superior hiding power, good solvent resistance, and strong high-temperature applicability. These properties allow them to impart ideal hues and ample protective functions to both organic and inorganic decorative products. Among these, blue pigments, as a mainstream pigment, exhibit unique spectral "reflection-absorption" characteristics—absorbing low-energy (i.e., long-wavelength) visible light in the red, orange, yellow, and green bands, while reflecting high-energy (i.e., short-wavelength) blue-violet light, thus displaying a rare blue hue. In terms of color realization, this is similar to many strongly colored direct bandgap semiconductor pigments (such as CaTaO2N, CdS...). 1-x Se x Blue pigments (such as HgS and Cu2O) are fundamentally different—the latter being related, primarily absorbing short-wavelength visible light while reflecting long-wavelength visible light. Therefore, this characteristic determines that blue pigments cannot achieve their vibrant blue hue through light absorption generated by direct bandgap energy level transitions, unlike red, orange, and yellow pigments. This factor is also a major reason why there is a relative scarcity of blue pigments with strong coloring capabilities, and why obtaining new blue pigments is extremely difficult.
[0003] In the existing technology, the variety of inorganic blue pigments is significantly inferior to that of other hues. Blue pigments are mainly composed of Co. 2+ As color-producing ions, they include spinel CoAl2O4 (and its doped derivative colorants), olivine Co2SiO4, phosphate Co3(PO4)2, and yttrium indium manganese blue YIn. 1-x Mn x O3, vanadium zirconium blue (V-ZrSiO4), iron blue (Prussian blue), ultramarine blue, and celestite blue (containing S3 particles). However, among the above inorganic blue pigments, vanadium zirconium blue (V-ZrSiO4) has a weaker blue color and is insufficient to display a deep hue under normal doping conditions (1-8 wt%); yttrium indium manganese blue (YIn) 1-x Mn x O3, Prussian blue, ultramarine blue, phosphate Co3(PO4)2, and celestite blue are unstable and easily decomposed, making them unsuitable for use in medium-high temperature environments of 600–1200℃. While spinel CoAl2O4 and olivine Co2SiO4 are widely used high-temperature blue pigments in the industry, their actual coloring largely originates from Co that has detached from the matrix CoAl2O4 or Co2SiO4 and dispersed in the glaze. 2+These two pigments, which are derived from ions rather than entirely from the pigment itself, have good stability when existing in pure phase on their own. However, their stability decreases significantly when applied to high-temperature environments, causing the pigment itself to change color and resulting in a large color difference. Therefore, they cannot be used in medium-high temperature environments of 600–1200℃. Summary of the Invention
[0004] The purpose of this invention is to provide an application of cobalt niobate-based material in blue pigments, a blue glaze and its preparation method. The cobalt niobate-based material provided by this invention can be used as a blue pigment in medium and high temperature environments of 600 to 1200°C, and the prepared blue glaze has a pure color tone.
[0005] To achieve the objectives of this invention, the following technical solutions are provided:
[0006] The application of a cobalt niobate-based material in blue pigments, wherein the chemical formula of the cobalt niobate-based material is: Co 1- x M x Nb₂O₆, where M is one of Mg, Ca, Zn, Sr and Ba; x is 0 to 1.
[0007] This invention also provides a method for preparing a blue glaze, comprising the following steps:
[0008] A cobalt niobate-based material, ceramic glaze, and water are mixed to obtain a mixed slurry; the chemical formula of the cobalt niobate-based material is: Co 1-x M x Nb2O6, wherein M and x are as defined in the above technical solution;
[0009] The mixed slurry is coated onto the ceramic surface to obtain a ceramic green body;
[0010] The ceramic blank is fired to obtain the blue glaze on the ceramic surface.
[0011] Preferably, the ceramic glaze is a transparent glaze at 1000℃.
[0012] Preferably, the mass ratio of the cobalt niobate-based material, ceramic glaze, and water is 1:10-15:12.5-20.
[0013] Preferably, the coating method is dip coating, spray coating or drop coating; the thickness of the mixed slurry coated on the ceramic surface is 1 to 3 mm.
[0014] Preferably, the firing temperature is 600–1200°C and the firing time is 0.5–2 hours.
[0015] Preferably, the preparation method of the cobalt niobate-based material includes the following steps:
[0016] CoCl2·6H2O, NbCl5, MCl2 and solvent were mixed to obtain a mixed solution;
[0017] The mixture and gelling agent are mixed, subjected to hydrothermal treatment and drying to obtain precursor powder;
[0018] The precursor powder is calcined to obtain the cobalt niobate-based material.
[0019] Preferably, the preparation method of the cobalt niobate-based material includes the following steps:
[0020] Nb2O5, Co(NO3)2·6H2O, MCl2 and molten salt were mixed and calcined to obtain the cobalt niobate-based material.
[0021] Preferably, the preparation method of the cobalt niobate-based material includes the following steps:
[0022] NbCl5, CoCl2·6H2O, MCl2 and an organic solvent were mixed and heat-treated to obtain a viscous gel.
[0023] The viscous gel was calcined to obtain the cobalt niobate-based material.
[0024] The present invention also provides a blue glaze prepared by the preparation method described in the above technical solution.
[0025] This invention provides an application of a cobalt niobate-based material in blue pigments, wherein the chemical formula of the cobalt niobate-based material is: Co 1-x M x Nb₂O₆, where M is one of Mg, Ca, Zn, Sr, and Ba; x is 0–1. In the cobalt niobate-based material of this invention, Co… 2+ The crystal structure and coordination of the pigment have a strong influence on the coloring intensity and hue of the pigment, among which Co... 2+ Located at a twisted octahedral site, the visible light absorption bands are mainly located in the red, orange, and yellow regions, reflecting most of the blue wavelength of visible light, thus displaying a purer blue; simultaneously, Nb 5+ It has a higher valence state, which can enhance the color stability of pigments in glazes. It can be used in medium and high temperature environments of 600 to 1200℃, and has excellent high temperature resistance and bright blue coloring characteristics. Attached Figure Description
[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0027] Figure 1 The XRD pattern of the blue CoNb2O6 material prepared in Example 1;
[0028] Figure 2 The UV-vis-NIR reflectance spectrum of the CoNb2O6 blue material prepared in Example 1;
[0029] Figure 3 Images of the CoNb2O6 blue pigment and the ceramic blue glaze prepared in Examples 3 and 4 are shown.
[0030] Figure 4 XRD patterns of the blue glaze on CoNb2O6 ceramics prepared in Examples 3 and 4;
[0031] Figure 5 Diffuse reflectance spectra of the CoNb2O6 blue material and the ceramic blue glaze prepared in Examples 3 and 4;
[0032] Figure 6 The diffuse reflectance spectra of the CoNb2O6 blue pigments prepared in Examples 1-4, Comparative Examples 1 and 2 are shown.
[0033] Figure 7 The XRD patterns of the CoNb2O6 blue pigments prepared in Examples 1-4, Comparative Examples 1 and 2 are shown.
[0034] Figure 8 The images show actual photos of the CoNb2O6 / CoAl2O4 blue pigment and the ceramic blue glaze prepared in Examples 3, 4, Comparative Examples 3 and 4.
[0035] Figure 9 The diffuse reflectance spectra of the blue glaze of CoNb2O6 / CoAl2O4 ceramics prepared in Examples 3, 4, 3, and 4.
[0036] Figure 10 The XRD patterns of the blue glaze on the CoNb2O6 / CoAl2O4 ceramics prepared in Examples 3, 4, 3, and 4 are shown. Detailed Implementation
[0037] This invention provides an application of a cobalt niobate-based material in blue pigments, wherein the chemical formula of the cobalt niobate-based material is: Co 1-x M x Nb₂O₆, where M is one of Mg, Ca, Zn, Sr and Ba; x is 0 to 1.
[0038] In this invention, the chemical formula of the cobalt niobate-based material is: Co 1-x Mx Nb2O6, wherein M is one of Mg, Ca, Zn, Sr and Ba; x is 0 to 1, preferably 0.05 to 0.2.
[0039] This invention also provides a method for preparing a blue glaze, comprising the following steps:
[0040] A cobalt niobate-based material, ceramic glaze, and water are mixed to obtain a mixed slurry; the chemical formula of the cobalt niobate-based material is: Co 1-x M x Nb2O6, wherein M and x are as defined in the above technical solution;
[0041] The mixed slurry is coated onto the ceramic surface to obtain a ceramic green body;
[0042] The ceramic blank is fired to obtain the blue glaze on the ceramic surface.
[0043] In this invention, unless otherwise specified, all raw materials used in the preparation are preferably commercially available products well known to those skilled in the art.
[0044] This invention mixes cobalt niobate-based material, ceramic glaze, and water to obtain a mixed slurry. In this invention, the ceramic glaze is preferably a 1000℃ transparent glaze. The preferred composition of the 1000℃ transparent glaze is: SiO 72.10 wt.%, Al₂O₃ 10.20 wt.%, B₂O₃ 2.41 wt.%, BeO 2.14 wt.%, ZnO 3.68 wt.%, K₂O 3.22 wt.%, CaO 2.23 wt.%, Fe₂O₃ 0.84 wt.%, Na₂O 1.95 wt.%, and MgO 1.23 wt.%. The preferred water in this invention is deionized water.
[0045] In this invention, the preparation method of the cobalt niobate-based material preferably includes the following steps:
[0046] CoCl2·6H2O, NbCl5, MCl2 and solvent were mixed to obtain a mixed solution;
[0047] The mixture and gelling agent are mixed, subjected to hydrothermal treatment and drying to obtain precursor powder;
[0048] The precursor powder is calcined to obtain the cobalt niobate-based material.
[0049] This invention involves mixing CoCl2·6H2O, NbCl5, MCl2, and a solvent to obtain a mixed solution. In this invention, when the Co... 1-x M xWhen x is 0 in Nb₂O₆, it is preferable to mix NbCl₅ with a first solvent to obtain an NbCl₅ solution; mix CoCl₂·6H₂O with a second solvent to obtain a CoCl₂ solution; and mix the CoCl₂ solution and the NbCl₅ solution to obtain a mixed solution. In this invention, the first solvent is preferably anhydrous methanol; the second solvent is preferably deionized water. In this invention, the mass ratio of NbCl₅ to the first solvent is preferably 13.51–17.56:60; the mass ratio of CoCl₂·6H₂O to the second solvent is preferably 5.95–7.73:30, more preferably 5.76–6.84:30. In this invention, the molar ratio of CoCl₂·6H₂O to NbCl₅ is preferably 1–1.30:2, more preferably 1.075–1.15:2.
[0050] In this invention, when the Co 1-x M x When x is not 0 in Nb₂O₆, it is preferable to mix NbCl₅ with the first solvent to obtain an NbCl₅ solution; mix CoCl₂·6H₂O, MCl₂, and the second solvent to obtain a CoCl₂-MCl₂ solution; and mix the CoCl₂-MCl₂ solution with the NbCl₅ solution to obtain a mixed solution. In this invention, M is preferably one of Mg, Ca, Zn, Sr, and Ba, more preferably Mg or Sr. In this invention, Co... 2+ With M 2+ The preferred molar ratio is 0-1:0-1, more preferably 0.2-0.95:0.2-0.05.
[0051] After obtaining the mixture, the present invention mixes the mixture with a gelling agent, performs hydrothermal treatment and drying to obtain a precursor powder. In the present invention, the gelling agent is preferably one or more of propylene oxide, citric acid, and ethylene glycol, more preferably propylene oxide. In the present invention, the molar ratio of the gelling agent to the total amount of metal ions participating in the reaction is preferably 1.84–4.59:1. In the present invention, the hydrothermal treatment temperature is preferably 60–80°C. The present invention does not have a specific limitation on the hydrothermal treatment time, as long as complete gelation is achieved. In the present invention, aging is preferably performed after the hydrothermal treatment. In the present invention, the aging temperature is preferably room temperature, and the aging time is preferably 2–3 hours. In the present invention, the drying temperature is preferably 120–150°C; the drying time is preferably 8–12 hours. In the present invention, grinding is preferably performed after drying.
[0052] After obtaining the precursor powder, the present invention calcines the precursor powder to obtain the cobalt niobate-based material. In the present invention, the calcination preferably includes a first calcination and a second calcination sequentially. In the present invention, the temperature of the first calcination is preferably 400–700°C, more preferably 600–650°C; the time is preferably 1–2 h, more preferably 1.5 h. The present invention removes organic carbon and chloride ion impurities through the first calcination. In the present invention, the temperature of the second calcination is preferably 900–1200°C, more preferably 1050–1100°C; the time is preferably 0.5–2 h, more preferably 1 h. In the present invention, the second calcination is preferably followed by grinding, washing, and sieving. The present invention does not specifically limit the grinding method; any grinding method well known to those skilled in the art can be used. In the present invention, the washing preferably includes sequential acid washing and water washing. In the present invention, the reagent used for acid washing is preferably one of hydrochloric acid, nitric acid, and acetic acid; the concentration of the reagent used for acid washing is preferably 1–3 mol / L. In this invention, the aperture of the sieve used for sieving is preferably 200 to 400 mesh.
[0053] In this invention, the method for preparing the cobalt niobate-based material preferably further includes the following steps:
[0054] Nb₂O₅, Co(NO₃)₂·6H₂O, MCl₂, and molten salt are mixed and calcined to obtain the cobalt niobate-based material. In this invention, the molten salt preferably comprises Li₂SO₄ and Na₂SO₄; the molar ratio of Li₂SO₄ to Na₂SO₄ is preferably 0.6–0.7:0.3–0.4, more preferably 0.635:0.365. In this invention, when the Co… 1-x M x When x in Nb₂O₆ is not 0, the molar ratio of Nb₂O₅, Co(NO₃)₂·6H₂O, MCl₂, and molten salt is preferably 2:0~1:0~1:1.5~4, more preferably 2:0.8~0.95:0.05~0.2:2~3. In this invention, when the Co… 1-x M x When x is 0 in Nb₂O₆, the molar ratio of Nb₂O₅, Co(NO₃)₂·6H₂O, and molten salt is preferably 2:1–1.3:1.5–4, more preferably 2:1:4. In this invention, the calcination temperature is preferably 800–1100℃, more preferably 1000–1050℃; the time is preferably 1–5 h, more preferably 2 h. In this invention, the calcination process preferably includes grinding and washing. In this invention, the grinding and washing are preferably the same as described above, and will not be repeated here. In this invention, Li in the molten salt is removed by grinding and washing. + and Na + .
[0055] In this invention, the method for preparing the cobalt niobate-based material preferably further includes the following steps:
[0056] NbCl5, CoCl2·6H2O, MCl2 and an organic solvent were mixed and heat-treated to obtain a viscous gel.
[0057] The viscous gel was calcined to obtain the cobalt niobate-based material.
[0058] This invention involves mixing NbCl5, CoCl2·6H2O, MCl2, and an organic solvent, followed by heat treatment to obtain a viscous gel. In this invention, the organic solvent preferably includes citric acid, ethylene glycol, and water; the mass ratio of citric acid, ethylene glycol, and water is preferably 10–20:20–40:20–60, more preferably 14:23:32.
[0059] In this invention, when the Co 1-x M x When x is 0 in Nb₂O₆, it is preferable to mix NbCl₅, CoCl₂·6H₂O, and an organic solvent. In this invention, the molar ratio of NbCl₅ to CoCl₂·6H₂O is preferably 2–2.5:1–1.5, more preferably 2:1.
[0060] In this invention, when the Co 1-x M x When x is not 0 in Nb₂O₆, it is preferable to mix NbCl₅, CoCl₂·6H₂O, MCl₂, and an organic solvent. In this invention, M is preferably one of Mg, Ca, Zn, Sr, and Ba, more preferably Zn, Ba, or Ca. In this invention, the molar ratio of NbCl₅ to CoCl₂·6H₂O is preferably 2:0 to 1, more preferably 2:0.8 to 0.95. In this invention, the molar ratio of NbCl₅ to MCl₂ is preferably 2:0 to 1, more preferably 2:0.05 to 0.2.
[0061] In this invention, the mixing of NbCl5, CoCl2·6H2O, MCl2, and the organic solvent is preferably carried out by stirring; the mixing time is preferably 0.5–1 h. In this invention, the heat treatment preferably includes a first heat treatment and a second heat treatment. In this invention, the temperature of the first heat treatment is preferably 60–70 °C; the time is preferably 1–2 h; the temperature of the second heat treatment is preferably 120–150 °C; the time is preferably 0.5–2 h. In this invention, the heating rate from the first heat treatment to the temperature required for the second heat treatment is preferably 5–10 °C / min.
[0062] After obtaining the viscous gel, the present invention calcines the viscous gel to obtain the cobalt niobate-based material. In the present invention, the calcination preferably includes a first calcination and a second calcination sequentially. In the present invention, the temperature of the first calcination is preferably 300–700°C, more preferably 350–600°C; the time is preferably 0.5–2 hours. The present invention removes organic carbon and chloride ion impurities through the first calcination. In the present invention, the temperature of the second calcination is preferably 900–1200°C, more preferably 1100°C; the time is preferably 1–1.5 hours. In the present invention, the second calcination is preferably followed by grinding and washing. In the present invention, the grinding and washing are preferably the same as those described above, and will not be repeated here.
[0063] In this invention, the viscous gel is preferably dried before calcination. The drying temperature is preferably 100–150°C, more preferably 120°C; the drying time is preferably 8–12 hours.
[0064] In this invention, the mass ratio of the cobalt niobate-based material, ceramic glaze and water is preferably 1:10-15:12.5-20, more preferably 1:12.5:15.
[0065] After obtaining the mixed slurry, the present invention coats the mixed slurry onto the ceramic surface to obtain a ceramic green body. In the present invention, the coating method is preferably one of dip coating, spray coating, and drop coating, more preferably dip coating. In the present invention, the dip coating time is preferably 8-10 seconds. In the present invention, the thickness of the mixed slurry coated on the ceramic surface is preferably 1-3 mm, more preferably 1.5-2 mm.
[0066] After obtaining the ceramic blank, the present invention fires the ceramic blank to obtain a blue glaze on the ceramic surface. In the present invention, the firing temperature is preferably 600-1200℃, more preferably 1000-1100℃; the firing time is preferably 0.5-2 hours.
[0067] The present invention also provides a blue glaze prepared by the preparation method described in the above technical solution.
[0068] To further illustrate the present invention, the application of the cobalt niobate-based material provided by the present invention in blue pigments and the preparation method of blue glaze are described in detail below with reference to the accompanying drawings and embodiments. However, these descriptions should not be construed as limiting the scope of protection of the present invention.
[0069] Example 1
[0070] Weigh 13.51g of NbCl5 and dissolve it in 60g of anhydrous methanol to obtain an NbCl5 solution; weigh 5.95g of CoCl2·6H2O and dissolve it in 30g of deionized water to obtain a CoCl2 solution; mix the above NbCl5 solution and CoCl2 solution thoroughly to obtain a mixed solution;
[0071] The above mixed solution was mixed with 8g of propylene oxide and hydrothermally treated at 60°C until it was completely gelled. Then it was allowed to stand at room temperature for 2 hours to obtain a colloid. The obtained colloid was crushed and transferred to a petri dish, dried at 150°C for 12 hours, and ground into a fine powder to obtain the precursor powder.
[0072] The precursor powder was placed in a corundum crucible and placed in a muffle furnace. It was calcined at 600℃ for 1.5 h, cooled and ground, and then calcined at 1050℃ for 1 h. The calcined powder was ground and then washed twice with 3 mol / L hydrochloric acid and three times with deionized water. After drying and grinding again, it was passed through a 200-mesh sieve to obtain CoNb2O6 blue material.
[0073] Example 2
[0074] Weigh 13.51g of NbCl5 and dissolve it in 60g of anhydrous methanol to obtain an NbCl5 solution; weigh 6.40g of CoCl2·6H2O and dissolve it in 30g of deionized water to obtain a CoCl2 solution; mix the above NbCl5 solution and CoCl2 solution thoroughly to obtain a mixed solution;
[0075] The above mixed solution was mixed with 10g of propylene oxide and hydrothermally treated at 60℃ until it was completely gelled. Then it was allowed to stand at room temperature for 2h to obtain a colloid. The obtained colloid was crushed and transferred to a petri dish, dried at 150℃ for 12h, and ground into a fine powder to obtain the precursor powder.
[0076] The precursor powder was placed in a corundum crucible and placed in a muffle furnace. It was calcined at 600℃ for 1.5 h, cooled and ground, and then calcined at 1050℃ for 1 h. The calcined powder was ground and then washed twice with 3 mol / L hydrochloric acid and three times with deionized water. After drying and grinding again, it was passed through a 200-mesh sieve to obtain CoNb2O6 blue material.
[0077] Example 3
[0078] Weigh 13.51g of NbCl5 and dissolve it in 60g of anhydrous methanol to obtain an NbCl5 solution; weigh 6.84g of CoCl2·6H2O and dissolve it in 30g of deionized water to obtain a CoCl2 solution; mix the above NbCl5 solution and CoCl2 solution thoroughly to obtain a mixed solution;
[0079] The above mixed solution was mixed with 10g of propylene oxide and hydrothermally treated at 60℃ until it was completely gelled. Then it was allowed to stand at room temperature for 2h to obtain a colloid. The obtained colloid was crushed and transferred to a petri dish, dried at 150℃ for 12h, and ground into a fine powder to obtain the precursor powder.
[0080] The aforementioned precursor powder was placed in a corundum crucible and calcined in a muffle furnace at 600℃ for 1.5 h. After cooling and grinding, it was calcined again at 1050℃ for 1 h. The calcined powder was then ground and washed twice with 3 mol / L hydrochloric acid, followed by three washes with deionized water. After drying and grinding again, it was passed through a 200-mesh sieve to obtain a blue CoNb2O6 material. (See image below.) Figure 3 As shown.
[0081] Example 4
[0082] Weigh 13.51g of NbCl5 and dissolve it in 60g of anhydrous methanol to obtain an NbCl5 solution; weigh 7.73g of CoCl2·6H2O and dissolve it in 30g of deionized water to obtain a CoCl2 solution; mix the above NbCl5 solution and CoCl2 solution thoroughly to obtain a mixed solution;
[0083] The above mixed solution was mixed with 10g of propylene oxide and hydrothermally treated at 60℃ until it was completely gelled. Then it was allowed to stand at room temperature for 2h to obtain a colloid. The obtained colloid was crushed and transferred to a petri dish, dried at 150℃ for 12h, and ground into a fine powder to obtain the precursor powder.
[0084] The aforementioned precursor powder was placed in a corundum crucible and calcined in a muffle furnace at 600℃ for 1.5 h. After cooling and grinding, it was calcined again at 1050℃ for 1 h. The calcined powder was then ground and washed twice with 3 mol / L hydrochloric acid, followed by three washes with deionized water. After drying and grinding again, it was passed through a 200-mesh sieve to obtain a blue CoNb2O6 material. (See image below.) Figure 3 As shown.
[0085] Example 5
[0086] Weigh 13.51g of NbCl5 and dissolve it in 60g of anhydrous methanol to obtain an NbCl5 solution; weigh 5.35g of CoCl2·6H2O and 2.5mmol of MgCl2·6H2O and dissolve them in 30g of deionized water to obtain a CoCl2-MgCl2 solution; mix the above NbCl5 solution and CoCl2-MgCl2 solution thoroughly to obtain a mixed solution;
[0087] The above mixed solution was mixed with 8g of propylene oxide and hydrothermally treated at 60°C until it was completely gelled. Then it was allowed to stand at room temperature for 2 hours to obtain a colloid. The obtained colloid was crushed and transferred to a petri dish, dried at 150°C for 12 hours, and ground into a fine powder to obtain the precursor powder.
[0088] The aforementioned precursor powder was placed in an alumina crucible and calcined in a muffle furnace at 600℃ for 1.5 h. After cooling and grinding, it was calcined again at 1050℃ for 1 h. The calcined powder was then ground and washed twice with 3 mol / L hydrochloric acid, followed by three washes with deionized water. After drying and grinding again, it was passed through a 200-mesh sieve to obtain Co. 0.9 Mg 0.1 Nb2O6 blue material.
[0089] Example 6
[0090] Weigh 13.51g of NbCl5 and dissolve it in 60g of anhydrous methanol to obtain an NbCl5 solution; weigh 5.35g of CoCl2·6H2O and 2.5mmol of SrCl2·6H2O and dissolve them in 30g of deionized water to obtain a CoCl2-SrCl2 solution; mix the above NbCl5 solution and CoCl2-SrCl2 solution thoroughly to obtain a mixed solution;
[0091] The above mixed solution was mixed with 8g of propylene oxide and hydrothermally treated at 60°C until it was completely gelled. Then it was allowed to stand at room temperature for 2 hours to obtain a colloid. The obtained colloid was crushed and transferred to a petri dish, dried at 150°C for 12 hours, and ground into a fine powder to obtain the precursor powder.
[0092] The aforementioned precursor powder was placed in an alumina crucible and calcined in a muffle furnace at 600℃ for 1.5 h. After cooling and grinding, it was calcined again at 1050℃ for 1 h. The calcined powder was then ground and washed twice with 3 mol / L hydrochloric acid, followed by three washes with deionized water. After drying and grinding again, it was passed through a 200-mesh sieve to obtain Co. 0.9 Sr 0.1 Nb2O6 blue material.
[0093] Example 7
[0094] Weigh 13.29g Nb2O5 and 7.28g Co(NO3)2·6H2O, grind and mix them thoroughly in an agate mortar to obtain a mixed powder. Mix 6.98g Li2SO4 and 5.18g Na2SO4 with the above mixed powder, put it into a corundum crucible and compact it, calcine it at 1050℃ for 2h, grind the calcined powder thoroughly, and then wash it twice with 3mol / L hydrochloric acid, and then wash it three times with deionized water. After drying, CoNb2O6 blue material is obtained.
[0095] Example 8
[0096] Weigh out 14g of citric acid, 23g of ethylene glycol and 32g of deionized water, mix them to obtain an organic solvent;
[0097] Weigh 5.0g NbCl5, 2.20g CoCl2·6H2O and the above organic solvent and stir for 30min. Then, perform hydrothermal treatment at 70℃ for 1h, and then heat treatment at 150℃ for 2h at a rate of 5℃ / min to obtain a viscous gel.
[0098] The above viscous gel was dried at 120℃ for 12 hours, then placed in a muffle furnace and calcined at 350℃ for 2 hours. After grinding, it was calcined at 1100℃ for 1.5 hours. After cooling to room temperature, it was ground again, then washed twice with 3mol / L hydrochloric acid, and then washed three times with deionized water. After drying, CoNb2O6 blue material was obtained.
[0099] Example 9
[0100] Weigh out 14g of citric acid, 23g of ethylene glycol and 32g of deionized water, mix them to obtain an organic solvent;
[0101] Weigh 5.0g NbCl5, 1.76g CoCl2·6H2O and 1.85mmol ZnCl2 and mix them with the above organic solvent for 30min. Then, perform hydrothermal treatment at 70℃ for 1h, and then heat treatment at 150℃ for 2h at a rate of 5℃ / min to obtain a viscous gel.
[0102] The above-mentioned viscous gel was dried at 120℃ for 12 hours, then placed in a muffle furnace and calcined at 350℃ for 2 hours. After grinding, it was calcined at 1100℃ for 1 hour. After cooling to room temperature, it was ground again, then washed twice with 3mol / L hydrochloric acid, and then three times with deionized water. After drying, Co was obtained. 0.8 Zn 0.2 Nb2O6 blue material.
[0103] Example 10
[0104] Weigh out 14g of citric acid, 23g of ethylene glycol and 32g of deionized water, mix them to obtain an organic solvent;
[0105] Weigh 5.0g NbCl5, 1.76g CoCl2·6H2O and 1.85mmol BaCl2 and mix them with the above organic solvent for 30min. Then, perform hydrothermal treatment at 70℃ for 1h, and then heat treatment at 150℃ for 2h at a rate of 5℃ / min to obtain a viscous gel.
[0106] The above-mentioned viscous gel was dried at 120℃ for 12 h, then placed in a muffle furnace and calcined at 350℃ for 2 h. After grinding, it was calcined at 1100℃ for 1.5 h, cooled to room temperature, and then ground again. The gel was then washed twice with 3 mol / L hydrochloric acid, followed by three washes with deionized water. After drying, Co was obtained. 0.8 Ba 0.2 Nb2O6 blue material.
[0107] Example 11
[0108] Weigh out 14g of citric acid, 23g of ethylene glycol and 32g of deionized water, mix them to obtain an organic solvent;
[0109] Weigh 5.0g NbCl5, 1.76g CoCl2·6H2O and 1.85mmol CaCl2 and mix them with the above organic solvent for 30min. Then, perform hydrothermal treatment at 70℃ for 1h, and then heat treatment at 150℃ for 2h at a rate of 5℃ / min to obtain a viscous gel.
[0110] The above-mentioned viscous gel was dried at 120℃ for 12 hours, then placed in a muffle furnace and calcined at 350℃ for 2 hours. After grinding, it was calcined at 1100℃ for 1 hour. After cooling to room temperature, it was ground again, then washed twice with 3mol / L hydrochloric acid, and then three times with deionized water. After drying, Co was obtained. 0.8 Ca 0.2 Nb2O6 blue material.
[0111] Example 12
[0112] Weigh 13.29g Nb2O5 and 7.28g Co(NO3)2·6H2O, grind and mix them thoroughly in an agate mortar to obtain a mixed powder. Mix 6.98g Li2SO4 and 5.18g Na2SO4 with the above mixed powder, put it into a corundum crucible and compact it, calcine it at 1050℃ for 2h, grind the calcined powder thoroughly, and then wash it twice with 3mol / L hydrochloric acid, and then wash it three times with deionized water. After drying, CoNb2O6 blue material is obtained.
[0113] Comparative Example 1
[0114] Weigh 15.54g of NbCl5 and dissolve it in 60g of anhydrous methanol to obtain an NbCl5 solution; weigh 5.95g of CoCl2·6H2O and dissolve it in 30g of deionized water to obtain a CoCl2 solution; mix the above NbCl5 solution and CoCl2 solution thoroughly to obtain a mixed solution;
[0115] The above mixed solution was mixed with 10g of propylene oxide and hydrothermally treated at 60℃ until it was completely gelled. Then it was allowed to stand at room temperature for 2h to obtain a colloid. The obtained colloid was crushed and transferred to a petri dish, dried at 150℃ for 12h, and ground into a fine powder to obtain the precursor powder.
[0116] The precursor powder was placed in a corundum crucible and placed in a muffle furnace. It was calcined at 600℃ for 1.5 h, cooled and ground, and then calcined at 1050℃ for 1 h. The calcined powder was ground and then washed twice with 3 mol / L hydrochloric acid and three times with deionized water. After drying and grinding again, it was passed through a 200-mesh sieve to obtain CoNb2O6 blue material.
[0117] Comparative Example 2
[0118] Weigh 17.56g of NbCl5 and dissolve it in 60g of anhydrous methanol to obtain an NbCl5 solution; weigh 5.95g of CoCl2·6H2O and dissolve it in 30g of deionized water to obtain a CoCl2 solution; mix the above NbCl5 solution and CoCl2 solution thoroughly to obtain a mixed solution;
[0119] The above mixed solution was mixed with 15g of propylene oxide and hydrothermally treated at 60°C until it was completely gelled. Then it was allowed to stand at room temperature for 2 hours to obtain a colloid. The obtained colloid was crushed and transferred to a petri dish, dried at 150°C for 12 hours, and ground into a fine powder to obtain the precursor powder.
[0120] The precursor powder was placed in a corundum crucible and placed in a muffle furnace. It was calcined at 600℃ for 1.5 h, cooled and ground, and then calcined at 1050℃ for 1 h. The calcined powder was ground and then washed twice with 3 mol / L hydrochloric acid and three times with deionized water. After drying and grinding again, it was passed through a 200-mesh sieve to obtain CoNb2O6 blue material.
[0121] Comparative Example 3
[0122] Weigh 24.14g of AlCl3 and dissolve it in 60g of anhydrous methanol to obtain an AlCl3 solution; weigh 11.90g of CoCl2·6H2O and dissolve it in 75g of deionized water to obtain a CoCl2 solution; mix the AlCl3 solution and the CoCl2 solution thoroughly to obtain a mixed solution;
[0123] The above mixed solution was mixed with 20g of propylene oxide and hydrothermally treated at 60℃ until it was completely gelled. Then it was allowed to stand at room temperature for 2h to obtain a colloid. The obtained colloid was crushed and transferred to a petri dish, dried at 150℃ for 12h, and ground into a fine powder to obtain the precursor powder.
[0124] The precursor powder was placed in a corundum crucible and placed in a muffle furnace. It was calcined at 600℃ for 1.5h, cooled and ground, and then calcined at 1050℃ for 1h. The calcined powder was ground and then washed twice with hydrochloric acid with a concentration of 1-3 mol / L, and then washed three times with deionized water. After drying and grinding again, it was passed through a 200-mesh sieve to obtain CoAl2O4 blue material.
[0125] Comparative Example 4
[0126] Commercial cobalt-aluminum blue pigment from Jiangxi Jinhuan Pigment Co., Ltd.
[0127] Application examples
[0128] 2g of CoNb2O6 blue material / CoAl2O4 blue material prepared in Examples 1-4 and Comparative Examples 1-4, 25g of ceramic glaze and 30g of deionized water were weighed and mixed to obtain a mixed slurry.
[0129] Hold a 30×30mm ceramic piece with tweezers and immerse the smooth side of the ceramic piece into the above-mentioned mixed slurry. The immersion thickness is 1.5mm, and the immersion time is 8-10 seconds to obtain a ceramic blank.
[0130] After the ceramic blanks were air-dried for 24 hours, they were placed in a muffle furnace and calcined. The temperature was increased to 1000℃ at a rate of 5℃ / min and fired for 0.5 hours to obtain a blue glaze on the ceramic surface.
[0131] Test case
[0132] The CoNb2O6 blue material / CoAl2O4 blue material and ceramic blue glaze prepared in Examples 1-4 and Comparative Examples 1-4 were characterized, and the results are shown below.
[0133] Figure 1 The XRD pattern of the blue CoNb2O6 material prepared in Example 1 is shown below. Figure 2 The UV-vis-NIR reflectance spectrum of the CoNb2O6 blue material prepared in Example 1 is shown below. Figures 1-2The results show that the main component of CoNb2O6 blue pigment, the CoNb2O6 phase, remains stable. Figure 2 As can be seen from the UV-vis-NIR reflectance spectrum, Co 2+ The fact that it remains at the octahedral site indicates that the CoNb2O6 structure is stable and will not be eroded by high-temperature glaze.
[0134] Figure 3 The images show actual samples of the CoNb₂O₆ blue pigment and the ceramic blue glaze prepared in Examples 3 and 4, respectively. The Co / Nb ratio is 1.15 / 2 for Example 3, and 1.30 / 2 for Example 4. Figure 3 The results show that after firing in high-temperature glaze, the CoNb2O6 blue material exhibits a bright and stable color.
[0135] Figure 4 The XRD patterns of the blue glaze on the CoNb₂O₆ ceramics prepared in Examples 3 and 4 are shown. The XRD pattern for the blue glaze on the CoNb₂O₆ ceramics prepared in Example 3 is Co / Nb = 1.15 / 2, and the XRD pattern for the blue glaze on the CoNb₂O₆ ceramics prepared in Example 4 is Co / Nb = 1.30 / 2. Figure 4 The results show that cobalt niobate remains stable after high-temperature firing in the glaze.
[0136] Figure 5 The diffuse reflectance spectra of the CoNb2O6 blue material and the ceramic blue glaze prepared in Examples 3 and 4 are shown. Sample 1 and Sample 1y are the diffuse reflectance spectra of the CoNb2O6 blue material and the ceramic blue glaze prepared in Example 3, respectively. Sample 2 and Sample 2y are the diffuse reflectance spectra of the CoNb2O6 blue material and the ceramic blue glaze prepared in Example 4, respectively. Figure 5 The results show that the blue glaze prepared from cobalt niobate exhibits a pure blue color, and the reflectance spectrum shows that Co... 2+ It still exists in octahedral coordination, and the color is stable.
[0137] Table 1 shows the chromaticity parameters of the CoNb2O6 blue pigment and ceramic blue glaze prepared in Examples 3 and 4.
[0138]
[0139] Note: The color parameters in Table 1 mainly include: lightness value L. * 0 to 100 correspond to black to white; redness value a * , representing the red-green saturation value; yellow saturation value b * , representing the yellow-blue tint value. Among them, b* A higher positive value indicates a higher yellowness value, while a lower negative value indicates a higher blueness value.
[0140] As shown in Table 1, the blueness value of the CoNb2O6 blue material and the blue ceramic glaze changes by less than 1, indicating that the color of CoNb2O6 in the ceramic glaze is very stable and the color difference is small. This proves that the cobalt niobate blue material prepared in this invention is a blue material that is resistant to high temperature corrosion and can be used in coloring fields with low, medium and high temperature ranges.
[0141] Figure 6 The diffuse reflectance spectra of the CoNb2O6 blue pigments prepared in Examples 1-4, Comparative Examples 1 and 2 are shown. Figure 7 The XRD patterns of the CoNb2O6 blue pigments prepared in Examples 1-4, Comparative Examples 1 and 2 are shown below. Co / Nb = 1 / 2, Co / Nb = 1.075 / 2, Co / Nb = 1.15 / 2, Co / Nb = 1.30 / 2, Co / Nb = 1 / 2.15, and Co / Nb = 1 / 2.30 correspond to Examples 1, 2, 3, 4, Comparative Examples 1 and 2, respectively. Figures 6-7 It can be seen that Co 2+ Increasing the content of cobalt niobate will enhance its reflection of blue light to some extent, but this is accompanied by a corresponding decrease in absorption; Nb 5+ An increase in content will affect the overall color of cobalt niobate. XRD results show that this adverse effect is mainly due to the formation of niobium oxide impurity phases.
[0142] Figure 8 The images show actual photos of the CoNb2O6 / CoAl2O4 blue material and the ceramic blue glaze prepared in Examples 3, 4, 3, and 4, respectively. Co / Nb = 1.15 / 2 and Co / Nb = 1.30 / 2 correspond to Examples 3 and 4, respectively. The experimentally prepared cobalt aluminum blue and commercial cobalt aluminum blue correspond to Examples 3 and 4, respectively. Figure 9 The diffuse reflectance spectra of the blue ceramic glaze of CoNb2O6 / CoAl2O4 prepared in Examples 3, 4, Comparative Examples 3 and 4 are shown, where 1y and 2y correspond to Examples 3 and 4, respectively, and A1 and A2 correspond to Comparative Examples 3 and 4, respectively. Figure 10 The XRD patterns of the blue ceramic glazes of CoNb2O6 / CoAl2O4 prepared in Examples 3, 4, Comparative Examples 3 and 4 are shown, where Co / Nb = 1.15 / 2 and Co / Nb = 1.30 / 2 correspond to Examples 3 and 4, respectively, and the experimentally prepared cobalt aluminum blue and commercially available cobalt aluminum blue correspond to Examples 3 and 4, respectively. Figures 8-10It can be seen that, compared with CoAl2O4 blue pigment, the CoNb2O6 blue pigment prepared by this invention has a purer color, which is consistent with the higher reflectance of cobalt niobate in the blue light region. After high-temperature glaze firing, the resulting ceramic blue glaze surface shows obvious differences. CoAl2O4 exhibits a significant color difference before and after firing, with a deep and dull color. Combined with XRD pattern analysis (unmarked peaks are substances in the glaze, which are difficult to locate), it is not difficult to find that this is most likely because most of the CoAl2O4 was eroded and decomposed by the glaze during firing, with some Co-O-Al being replaced by Co-O-Si and Co... 3+ The increase in concentration leads to changes in the crystal field environment. Therefore, a noticeable color difference occurs between the pigment powder and the glaze product. Conversely, the bright and vivid characteristics of CoNb2O6 blue pigment are maintained by the stable presence of the main CoNb2O6 phase before and after firing at 1000–1200℃, resulting in very stable color.
[0143] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. The application of a cobalt niobate-based material in blue pigments, characterized in that, The chemical formula of the cobalt niobate-based material is: Co 1-x M x Nb₂O₆, where M is one of Mg, Ca, Zn, Sr and Ba; x is 0~0.
2.
2. A method for preparing a blue glaze, characterized in that, Includes the following steps: A cobalt niobate-based material, ceramic glaze, and water are mixed to obtain a mixed slurry; the chemical formula of the cobalt niobate-based material is: Co 1-x M x Nb₂O₆, where M is one of Mg, Ca, Zn, Sr and Ba; x is 0~0.2; The mixed slurry is coated onto the ceramic surface to obtain a ceramic green body; The ceramic blank is fired to obtain the blue glaze on the ceramic surface.
3. The preparation method according to claim 2, characterized in that, The ceramic glaze is a transparent glaze at 1000℃.
4. The preparation method according to claim 3, characterized in that, The mass ratio of the cobalt niobate-based material, ceramic glaze, and water is 1:10~15:12.5~20.
5. The preparation method according to claim 2, characterized in that, The coating method is dip coating, spray coating, or drip coating; The thickness of the mixed slurry coated on the ceramic surface is 1~3mm.
6. The preparation method according to claim 2, characterized in that, The firing temperature is 600~1200℃, and the firing time is 0.5~2h.
7. The preparation method according to claim 2, characterized in that, The preparation method of the cobalt niobate-based material includes the following steps: CoCl2·6H2O, NbCl5, MCl2 and solvent were mixed to obtain a mixed solution; The mixture and gelling agent are mixed, subjected to hydrothermal treatment and drying to obtain precursor powder; The precursor powder is calcined to obtain the cobalt niobate-based material.
8. The preparation method according to claim 2, characterized in that, The preparation method of the cobalt niobate-based material includes the following steps: Nb2O5, Co(NO3)2·6H2O, MCl2 and molten salt were mixed and calcined to obtain the cobalt niobate-based material.
9. The preparation method according to claim 2, characterized in that, The preparation method of the cobalt niobate-based material includes the following steps: NbCl5, CoCl2·6H2O, MCl2 and an organic solvent were mixed and heat-treated to obtain a viscous gel. The viscous gel was calcined to obtain the cobalt niobate-based material.
10. A blue glaze prepared by the method for preparing blue glaze according to any one of claims 2 to 9.
Citation Information
Patent Citations
New inorganic blue pigments from cobalt doped magnesium having transition element oxides and a process for the preparing the same
CN106414618A
